North Atlantic Oscillation response to the Madden–Julian Oscillation in a coupled climate model. (30th May 2022) - Skinner, Daniel T.; Matthews, Adrian J.; Stevens, David P.
Abstract : Understanding and predicting the state of the North Atlantic Oscillation (NAO) is key to forecasting the weather in the United Kingdom (UK). It has been shown that particular phases of the Madden–Julian Oscillation (MJO) act as precursors to either NAO+ or NAO− events. We assess the ability of the UK Met Office coupled climate model (HadGEM3‐GC3.1‐MM) to simulate these NAO responses at lead times of 1–2 weeks and show that improvements are needed in the modelling of MJO teleconnection patterns.